PENINGKATAN KAPASITAS MAHASISWA PMI STAIN MEULABOH DALAM MENYUSUN JURNAL PENGABDIAN BERBASIS LAPORAN PPL MIKRO DAN MAKRO - Syahputra, Andi; Efendi, Sumardi; Paisal, Jon; Ramli, Ramli; Sukri, Sukri; Muriza, Neza; Reyza, Reyza; Azizah, Azizah; Ruqayyah, Siti; Putra, Bachrum Syah (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
This activity aims to enhance the capacity of students from the Islamic Community Development (PMI) Study Program at STAIN Teungku Dirundeng Meulaboh in writing community service journals based on their micro and macro Field Practice Experience (PPL) reports. The background of this initiative lies in the students’ limited awareness and skills in transforming PPL reports into publishable scientific articles. The method employed in this program was the Participatory Action Research (PAR) approach, conducted through three main stages: problem identification, training and mentoring in journal writing, and evaluation of outcomes. The activity featured two resource persons: Ramli, M.Ag (PMI Lecturer), and Sumardi Efendi, M.Ag (Islamic Criminal Law Lecturer), who have collaboratively published 24 community service journals with students since 2022. The results show that students gained a deeper understanding of the structure, writing techniques, and ethical aspects of scientific publication. They were also encouraged to actively document their PPL activities in a systematic and scholarly manner. This initiative serves as a strategic effort to foster a scientific culture among PMI students.